Development of methods to control quality of the structure of cross-wound packages - Nuriyev, Mahammadali Nuraddin; Seydaliyev, Ilham Mammad (Eastern-European Journal of Enterprise Technologies, 2018)
The process of winding is one of the principal processes in the textile industry. Quality of the formed packages largely defines the quality of the finished product in the textile industry, as well as labor productivity and equipment performance. Therefore, attention to analysis of processes of package formation, construction of new promising methods and designs of winding mechanisms, has been growing for many decades. We address issues related to the analysis of control methods over the structure of the cross-wound winding used in spinning production. The structure of winding is understood in the present work as the mutual arrangement of threads when they are laid on the surface of the package. Thus, the parameters of the structure include such quantities as a turn lifting angle, a distance between the points of turn reversal, a step in turns, etc. It is known that the mutual arrangement of turns on the winding body when packages are frictionally driven is not homogeneous. Under certain ratios between rotation speed of the bobbin and motion frequency of the thread guide, the threads are laid on the same place. In this case, the so-called braid formations are observed. If motion frequencies of the bobbin and the thread guide differ slightly from the multiple ones, turns are placed close to each other, in this case, a tape winding is formed. The braid winding is accompanied by a number of phenomena, which negatively affect quality of the formed packages. In this case, the shear and displacement parameters are determined based on empirical data. To substantiate the approach to choosing the technological parameters for such mechanisms, we performed a theoretical analysis of the process of braid structures formation in terms of the force interactions between threads. To make such a choice, it is necessary to have an instrumental procedure for quantifying the winding structure parameters, which is why we have in detail investigated methods for their registration.